Home Yards Utilization in Providing Independence and House Food Security at Sidodadi Village, Tempurejo District, Jember Regency: Pemanfaatan Lahan Pekarangan Untuk Mewujudkan Kemandirian dan Ketahanan Pangan Rumah Tangga di Desa Sidodadi Kecamatan Tempurejo Kabupaten Jember - Fatimatuzzahro; Tria Anggraini; Rifqi Putra Al Ghifari; Rizka Nur Istiqomah; Muhamad Faza Fil Khaunaini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Community empowerment in the Collaborative Community Service Program (KKN) #3 Group 044 aims to realize food security in Jember Regency. The problem raised concerns the utilization of yard land with polybag planting media in Sidodadi Village, Tempurejo District. This activity aims to provide an understanding to the people of Krajan Hamlet, Mandiku Hamlet, and Jatirejo Hamlet, how to utilize home yards to realize food independence and security. The types of plants are mustard greens, chilies, broccoli, and tomatoes. The empowerment method used is Participatory Action Research. The stages of implementation are problem identification, action planning, implementation, observation, and collaborative learning. The results of this activity are to increase residents' knowledge about vegetable cultivation, as well as how to maintain them, and provide education about the utilization of residents' home yards in realizing household food security through polybag plant cultivation. Sidodadi Village residents actively participate in plant cultivation activities. The activity of utilizing residents' home land in vegetable cultivation is expected to be sustainable so that it can be used as a provider of nutritious food or even a source of income for residents.